Education on Healthy Diet and Physical Activity in Controlling Cholesterol Levels in Middle Adulthood (JURNAL PENGMAS KESTRA (JPK), 2025)
Dyslipidemia, particularly elevated LDL cholesterol, is a major risk factor for cardiovascular disease, the prevalence of which increases with advancing age and changes in lifestyle. Non-pharmacological interventions such as dietary changes and increased physical activity are affordable primary strategies for controlling cholesterol levels in the middle-aged adult population. Elevated cholesterol levels, particularly low-density lipoprotein (LDL), are a major risk factor for cardiovascular disease, often found in middle-aged adults. This condition is closely related to an unbalanced diet and low physical activity. Efforts to control cholesterol through non-pharmacological approaches, such as education on healthy eating patterns and regular physical activity, are important promotive and preventive strategies in public health services. This community service activity aims to increase knowledge and healthy behaviors and reduce cholesterol levels in middle-aged adults through education on healthy eating patterns and physical activity. The method used is a structured, community-based education program that includes nutrition counseling, assistance in implementing healthy eating patterns, and regular moderate-intensity aerobic physical activity training. Evaluation is carried out by measuring knowledge and lipid profiles before and after the intervention. The results of the community service implementation showed an increase, the respondent's knowledge score increased from 45% before education to 85% after education, this shows an increase of 40 percentage points and the average total cholesterol level of respondents decreased from 235 mg / dL before the intervention to 212 mg / dL after the intervention, with a decrease of 23 mg / dL (± 9.8%), Changes in healthy behavior were also seen from the increasing proportion of respondents who did light-moderate physical activity for at least 150 minutes / week from 35% to 78%, as well as an increase in vegetable and fruit consumption from 25% to 75%. These findings are in line with various intervention studies and meta-analyses which state that the combination of nutrition education and physical activity has a more effective impact on improving lipid profiles than single interventions. Healthy eating education integrated with regular physical activity is effective as an effort to control cholesterol levels in middle adulthood. Community education-based community service programs have the potential to be a sustainable promotive-preventive intervention model in reducing the risk of cardiovascular disease in the community.